Enviroshopping for Teens - Linda B. Bobroff; R. Elaine Turner (EDIS)
This document is FCS8756, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2000. Reviewed: August 2002.